Neudesin as a unique secreted protein with multi-functional roles in neural functions, energy metabolism, and tumorigenesis - Ohta, Hiroya; Kimura, Ikuo; Konishi, Morichika; Itoh, Nobuyuki (Frontiers in Molecular Biosciences, 2015)
Neudesin was originally identified as a secreted protein with neurotrophic activity, and, thereafter, was also termed neuron-derived neurotrophic factor (NENF) or the candidate oncogene GIG47. Neudesin with a conserved cytochrome 5-like heme/steroid-binding domain activates intracellular signaling pathways possibly through the activation of G protein-coupled receptors. In the brain, hypothalamic Neudesin decreases food intake. Neudesin knockout mice also exhibit anxiety-like behavior, indicating its roles in the hippocampal anxiety circuitry. Neudesin is also expressed in various peripheral tissues. Neudesin knockout mice are strongly resistant to high-fat diet-induced obesity due to elevated systemic sympathetic activity, heat production, and adipocytic lipolysis. Neudesin, which is over-expressed or induced by DNA hypomethylation in multiple human cancers, also stimulates tumorigenesis. These findings indicate that Neudesin plays roles in neural functions, energy metabolism, and tumorigenesis and is expected to be a novel target for obesity and anti-cancer treatments.